Profil Peternakan Domba Sistem Kemitraan dan Faktor-faktor yang Memengaruhi Pendapatan Peternak Mitra - Kahfi, Muhammad Alif Nur; Amam, Amam; Jadmiko, Mochammad Wildan; Harsita, Pradiptya Ayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The plasma core partnership-based sheep fattening business in Bondowoso Regency is a form of collaboration between partner breeders and core companies, as a form of livestock business sustainability in increasing global competitiveness. The core plasma partnership program for sheep fattening encourages farmers to guarantee an appropriate market share and increases farmers' income. This research aims to analyze operational costs, farmer income, and factors that influence the plasma core partnership system sheep fattening business. The research variables consist of farmer income (Y), livestock population (X1), weight difference (X2), daily body weight gain (X3), feed consumption (X4), and feed consumption costs (X5). The research was conducted at UD. Alfatih Multi Farm Petung Village, Curahdami District, Bondowoso Regency, East Java Province. Data analysis used SPSS 26.0 and Microsoft Excel software. The research results showed that the operational costs of 104 sheep breeders with ownership of 4,023 sheep with an average livestock weight of 20 Kg and feed consumption of 173,237 Kg and feed consumption costs of 3500/Kg, then the operational costs of 104 sheep breeders with a core plasma partnership system in Bondowoso Regency amounting to IDR 787,364,500. With an average operational cost for 1 farmer of IDR 7,570,812.5 for a maintenance period of 2 months (60 days). The income of sheep breeders is 104 partner breeders with farmer income of IDR 390,613,550, ownership of 4,023 sheep with an average livestock weight of 20 Kg and feed consumption of 173,237 Kg and feed consumption costs of 3500/Kg. So the income of 104 sheep farmers with the core plasma partnership system in Bondowoso Regency is IDR 396,750,950. With an average income of 1 farmer of IDR 3,814,912.9 in a maintenance period of 2 months (60 days). The number of livestock populations is positively but not significantly influenced by breeder income by 0.924, the weight difference is positively but not significantly influenced by breeder income by 0.381, daily body weight gain is positively but not significantly influenced by breeder income by 0.291, feed consumption is positively influenced and significant to the farmer's income of 0.000, and the cost of feed consumption is positively influenced but not significant to the farmer's income of 0.120. The conclusion of this research is that operational costs, farmer income, and the factors that influence them influence the sustainability of the plasma core partnership system sheep fattening business in Bondowoso Regency.